2002
DOI: 10.1677/joe.0.1720045
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-alpha6beta1 integrin interaction enhances survival and proliferation and modulates steroidogenesis of ovine granulosa cells

Abstract: This study aimed to determine the physiological role of laminin (LN) and its receptor, 6 1 integrin, in controlling the functions of granulosa cells (GC) during follicular development in sheep ovary. Immunohistochemistry experiments showed the presence of increasing levels of LN (P<0·0001), and high levels of mature 6 1 integrin in GC layers of healthy antral follicles during the follicular and the preovulatory phases of the estrous cycle. In vitro, the addition of a function-blocking antibody raised against 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 55 publications
1
49
0
1
Order By: Relevance
“…Integrin a6/b1 is the receptor for laminin on GCs and it has been shown that the interaction between them in GCs enhances survival and proliferation and modulates steroidogenesis (Le Bellego et al, 2002). Whether the ITGA6 antisense lncRNA directly regulates the expression of its ITGA6 host gene requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin a6/b1 is the receptor for laminin on GCs and it has been shown that the interaction between them in GCs enhances survival and proliferation and modulates steroidogenesis (Le Bellego et al, 2002). Whether the ITGA6 antisense lncRNA directly regulates the expression of its ITGA6 host gene requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…With continued in vitro culture, the expression of many parts of these genes is enhanced in the AF group. In addition, ITGA6, THBS1, THBS2, VEGF, AMH, FST and INHBA were reported to express high in growing follicles (Le Bellego et al 2002, Nilsson et al 2003, Greenaway et al 2005, Tesfaye et al 2009, Rosales-Torres et al 2010, Bonnet et al 2011 and Table 5 Expression of marker genes in granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the follicles were classified according to their size: 1-3, 3-5, 5-8, and O8 mm. Follicular fluids and granulosa cells were recovered from the follicles of both ovaries in each goat, as described previously (Le Bellego et al 2002). For each goat, the follicular fluids were pooled according to the size of the follicles (one to three pools of follicular fluids per follicular size class, when follicles of the size class were present) and stored at K20 8C until the AMH assay was performed.…”
Section: Plasma Follicular Fluid and Granulosa Cell Collectionmentioning
confidence: 99%